2019
DOI: 10.1136/bmjopen-2018-022478
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for thromboembolic and bleeding events in anticoagulated patients with atrial fibrillation: the prospective, multicentre observational PREvention oF thromboembolic events - European Registry in Atrial Fibrillation (PREFER in AF)

Abstract: ObjectivesWe identified factors associated with thromboembolic and bleeding events in two contemporary cohorts of anticoagulated patients with atrial fibrillation (AF), treated with either vitamin K antagonists (VKA) or non-VKA oral anticoagulants (NOACs).DesignProspective, multicentre observational study.Setting461 centres in seven European countries.Participants5310 patients receiving a VKA (PREvention oF thromboembolic events - European Registry in Atrial Fibrillation (PREFER in AF), derivation cohort) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 42 publications
2
54
5
2
Order By: Relevance
“…Age over 75 years is generally reported as a risk factor for increased GIT bleeding [2,8,22,25], but this trend was not observed in our series. We also did not record an increased incidence of bleeding depending on the dose of NOACs.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Age over 75 years is generally reported as a risk factor for increased GIT bleeding [2,8,22,25], but this trend was not observed in our series. We also did not record an increased incidence of bleeding depending on the dose of NOACs.…”
Section: Discussioncontrasting
confidence: 87%
“…The risk factors for bleeding are considered previous bleeding in the GIT, history of gastroduodenal ulcer, age, hypertension, heart failure, smoking, male gender, anemia, chronic obstructive bronchopulmonary disease, impaired renal and liver function, and concomitant use of antiplatelets agents or non-steroidal anti-inflammatory drugs. The risk of GIT bleeding is the highest within the first three months of treatment [2,3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We found that only age and coronary artery disease were associated with embolic events in this sample of anticoagulated patients with AF aged 80 years. Previous observational and post hoc analysis of clinical trials including octogenarians 13 and a wider spectrum of age 23,24 have found those variables to be associated with this outcome, as well as other factors, as chronic kidney disease, 13 that we have not been able to confirm, possibly due to lack of statistical power. Renal failure, previous severe bleeding, and EHRA functional class II were independently associated with severe bleeding in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Atrial fibrillation (AF) is the most common arrhythmia worldwide 1. It is associated with a fourfold to fivefold increased risk of ischaemic stroke 2 3. Known or new-onset AF is a common comorbidity in patients with acute coronary syndrome (ACS).…”
Section: Introductionmentioning
confidence: 99%